Radikalisme pada World Wide Web dan Strategi Propaganda - Nurdin Nurdin (Al-Ulum, 2016)
Radical individual and organizations are setting strong foothold on Internet. They operate in dark network hidden from authorities view to pursuade, recruit, and coordinate radical and violent actions. The presence of radical individual and organizations onInternet sites have caused massive debate and contraversi among Internet users, law enforcement bodies,and policy makers regarding misuse of Internet. However, little is known how exactly radical individual and organizations deliver their propaganda on Internet and what radical organizations practice such activities on Internet. Through the use of content analysis approach, this study analyzed various radical websites content to provide deep insight of radical operation and propaganda on Internet. Data was collected from various popular radical organization websites and previous studies. The findings show that well-kown organized radical and terorist oragnizations in Indonesia and International have intensively used Internet for new arena to radical and terror public across the globe. They use Internet topursuade, deliver propaganda to a global audience, recruit new members, communicate with international supporters, solicit donations, and fostering public awareness. This study concludes that Internet has become a new instrument to spread radicalism and terror within community life.